New technique "Right Anterior Small Thoracotomy (RAST operation)" for beating heart grafting of the right internal thoracic artery to the posterior descending artery to the posterior descending artery in a third redo CABG patient. A novel coronary technique - Guida,Maximo (2014)
Third REDO-CABG is a challenge for the surgical team. Usually a patent mammary is the only graft working and the sternotomy becomes a risky procedure. Injury to a patent graft has been associated to a high mortality rate. Many different approaches have been proposed. We describe a novel technique to approach the right coronary artery through a right anterior small thoracotomy using the right mammary prolonged with saphenous vein for grafting the posterior descending artery on the beating heart. The technique is very simple and feasible because anatomically the right coronary artery and the right mammary are very close and the mobilization of the heart is minimal.